PENGGUNAAN KLAUSA RELATIF DALAM ARTIKEL “RAGAM PERMAINAN DALAM PEMBELAJARAN BERBICARA BIPA” OLEH RENI ARTANA - Shafariana Shafariana (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This qualitative descriptive research focuses on relative clauses found in the functions of subject, predicate, and object. Relative clauses from